Aggregate index of systemic inflammation and glaucoma status: population-based evidence with clinical validation - Songxin Yang; Li Li; Xianming Ouyang; Rui Zhang; Gang Lin; Sunkun Pan; Guiquan Xie; Zhen Lv; Dieran Huang; Guoyan Luo; Kunpeng Pang (Frontiers in Medicine, 2026)
Objective Glaucoma is a major cause of irreversible visual impairment, but evidence on the association between the aggregate index of systemic inflammation (AISI) and glaucoma remains limited, particularly with clinical validation. Methods We analyzed National Health and Nutrition Examination Survey (NHANES) data from participants aged 40 years and older. Weighted multivariable logistic regression models were used to examine the association between AISI and glaucoma. The primary outcome was composite glaucoma, defined as the presence of either self-reported glaucoma or examination-based glaucoma; the two definitions were also analyzed separately in sensitivity analyses. Additional sensitivity analyses excluded participants with extreme AISI values and, separately, participants with a white blood cell (WBC) count >10 × 10 9 /L. We also compared AISI with related blood-cell-derived inflammatory indices and applied false discovery rate correction for multiple comparisons. Finally, the main findings were validated using a hospital-based clinical sample. Results The primary analysis included 5,455 participants, among whom 431 had composite glaucoma. After full adjustment, each doubling of AISI was associated with higher odds of composite glaucoma (OR = 1.20, 95% CI: 1.05–1.37, P = 0.016). Compared with the lowest quartile, the highest quartile was associated with higher odds of composite glaucoma (OR = 1.66, 95% CI: 1.12–2.46, P = 0.026), and the trend test was statistically significant ( P for trend = 0.037). Findings for self-reported glaucoma were consistent in direction and statistically significant, whereas examination-based glaucoma showed a consistent direction but weaker statistical evidence. The association remained statistically significant after excluding participants with WBC counts >10 × 10 9 /L. After false discovery rate correction, AISI and SIRI remained significantly associated with composite glaucoma. In the clinical sample, AISI levels were higher in patients with primary glaucoma than in the control groups. Conclusions Higher AISI was associated with higher odds of glaucoma among adults. As a blood-cell-derived inflammatory index based on routine peripheral blood counts, AISI may provide complementary evidence linking systemic inflammatory burden with glaucoma status. The clinical validation sample further supported this association.